Implementation of Islamic Education Based on Religious Moderation Through Tri Dharma Activities at Islamic Religious College - M. Suyudi; Wahyu Hanafi Putra (STAI Hubbulwathan Duri, 2022)
This study aimed to describe the implementation of Islamic education based on religious moderation at the Islamic Institute in Ponorogo through education, research, and community service activities. This type of research was qualitative with a case study model. The study results stated that the implementation of Islamic education based on religious moderation Ponorogo by redesigning the KKNI 2016 Graduation Achievements and Graduate Competency Standards of each Study Program and aligned with the institute's vision and mission. The result of the implementation is the distribution of Islamic sciences courses that understand Ahlusunnah wal Jama'ah to each Study Program as an introductory course in understanding comprehensive Islam. The performance of research based on religious moderation is carried out with a focus on Interdisciplinary Islamic Studies divided into sub-Tarbiyah and Education, Islamic Law and Economics, and Da'wah and Social. Then, the field of community services based on religious moderation is carried out through Islamic community organizations, Community Service Lectures, and Social Services.